Novel antifouling paint formulation based on Ca2​Cr2O5​ and CaMnO3​ NPs as a protective pigment - H. Abd El-Wahab; Hossa F. Al-Shareef (Scientific Reports)
Abstract This work focused on the preparation of novel antifouling paint based on Ca2Cr2O5 and CaMnO3 NPs as a safe protective pigment which were replaced with cuprous oxide. Three paint formulations were prepared for comparison, a blank formula without an antifouling agent (F1), a commercial antifouling formula based on 100% cuprous oxide as an antifouling agent (F2), and AF formula based on 75% Ca2Cr2O5 and CaMnO3 NPs and 25% Cu2O. The high performance and durability of the paints based on the prepared pigments were evident from their impact resistance, adhesion, pending, hardness, and chemical resistance, which were compared to the blank formula (F1). The corrosion resistance of the painted films was also investigated using the salt spray test method, and the results were promising compared to the blank and standard formulations. All painted steel plates were exposed to seawater through field tests in the Suez Canal at Port Said for up to 6 months. The results showed that the paints based on F2 and F3a, b enhanced the antifouling activity through six months of exposure. The obtained results demonstrated greater efficiency of the painted steel-based F3a than F1 and F3b, and being comparable to the standard formula (F2).